The fluid and thermal dynamics of rimming flows with boundary slip - Nicholson, Jonathon M. P. (2020)
This thesis intends to provide the reader with a detailed understanding of the current research into aero-engine bearing chambers, providing a description of their function and importance to the aerospace industry. The bearing chambers are a complex component where there is a chaotic mix of oil droplets, splashing, heating and geometric complexities which makes conventional analysis techniques costly to implement. The aim of this research is to describe the important physical effects pertinent to the rotational flow found in bearing chambers within a mathematical modelling strategy.